Experimental study on the effect of cover and vaccination on the survival of juvenile European rabbits. Issue 1 (20th September 2013) - Ferreira, Catarina; Villafuerte, Rafael; Villar, Nacho; Castro, Francisca; Ferreras, Pablo; Rouco, Carlos; Alves, Paulo C.; de Reyna, Luis Arias; Redpath, Steve
Abstract: In Mediterranean ecosystems, the European rabbit is a keystone species that has declined dramatically, with profound implications for conservation and management. Predation and disease acting on juveniles are considered the likely causes. In the field, these processes are managed by removing predators, increasing cover to reduce predation risk and by vaccinating against myxomatosis. These manipulations can be costly and, when protected predators are killed, they can also be damaging to conservation interests. Our goal was to test the effectiveness of cover and vaccination on juvenile survival in two large enclosures, free of mammalian predators, by adding cover and vaccinating juveniles. Rabbit warrens were our experimental unit, with nine replicates of four treatments: control, cover, vaccination, and cover and vaccination combined. Our results showed that improved cover systematically increased juvenile rabbit survival, whereas vaccination had no clear effect and the interactive effect was negligible. Our experimental data suggest that improved cover around warrens is an effective way of increasing rabbit abundance in Mediterranean ecosystems, at least when generalist mammalian predators are scarce. In contrast the vaccination programme was of limited benefit, raising questions about its efficacy as a management tool.